Analisis Preferensi Wisatawan Terhadap Pilihan Berwisata Di Sendang Sombomerti Depok Sleman Yogyakarta - Atun Yulianto; Wisnu Hadi; Yulianto (STIE Pariwisata API Yogyakarta, 2023)
The lack of information about the beauty of Sombomerti spring in the community is one of the factors that cause people's choice of traveled Sombomerti is still low. This research on Sendang Sombomerti Yogyakarta aims to determine the effect of tourist preferences related to ticket prices, accessibility, beauty, facilities, information and service quality on community traveled choices at Sendang Sombomerti. This research design uses quantitative methods supported by surveys. The population in this research is tourists sendang sombomerti with a quota system sampling of 50 respondents. The research instrument for collecting research data was submitted in the form of questionnaire questions to respondents with the size of the answer adopting the Likert scale. Observation and documentation of secondary data from similar research were also used to clarify the analysis. This research result indicates that on this fact of the six tourists variable preference study, there are two variables significant impact on choice sendang sombomerti traveled in light of beauty and customer service. While together the six researched tourist preference variables can significantly affect the field trip options at sombomerti.